The right to non-violence against women: the Costa Rican state as an accomplice to its failure to comply - Araya Umaña, Sandra (2019)
The tension between children's rights and those of women who are victims of violence within the so-called special processes for the protection of children in administrative headquarters are synthesized in this article, based on the completion of a case study in Costa Rica, during the period between 2017 and first quarter of 2018. In the field of childhood, the expression of the state’s patriarchal fissures and contradictions regarding its commitment to the human rights of women to a life free of violence was the main finding. These women mostly face state violence concealed in the myth of the good mother, in the figure of the best interests of childhood and in a conservative instrumentality, in addition to experiencing their partner's violence. Likewise, challenges arise in the study of the promotion of human rights from a gender perspective, since in the scenario studied the social demands associated with motherhood are placed at the center of intervention (and prosecution), covering up the perverse strands of a state which, in essence, maintains intact its patriarchal and classist structure.